Genetic diversity in ornamental pepper plants - Fortunato, Flávia Laís Gomes; do Rêgo, Elizanilda Ramalho; de Carvalho, Michelle Gonçalves; dos Santos, Cristine Agrine Pereira; do Rêgo, Mailson Monteiro (Comunicata Scientiae, 2019)
The genus Capsicum comprises a wide variety of peppers and peppers, with different sizes, colors and flavors. The present work had the objective to characterize and evaluate the genetic divergence among eight accessions of pepper (Capsicum annuum). The experiment was developed at the Federal University of Paraíba, Areia - PB. Eight accessions of pepper belonging to the germplasm bank of the CCA-UFPB were used. The experimental design was completely randomized. Data were submitted to analysis of variance by the F test at a level of 5% and 1% significance and the means were grouped by the Scott Knott test at 5% and 1% significance. For the analysis of genetic divergence, the Tocher grouping method and canonical variables were used. The treatment effects were significant, by the F test, at a level of 1% for all the characteristics evaluated, except for crown width and stem diameter, which were significant at 5% probability. According to the results obtained in the Scott & Knott test at 5% and 1% probability, the accessions were differentiated into two to six different classes. According to Tocher’s methodology the accessions were grouped into two groups. In the analysis of the canonical variables, the first three variables explained 94.18% of the total variance, and four different groups were formed according to the graphical dispersion.